GRAS-microparticle microarrays identify dendritic cell tolerogenic marker-inducing formulations. Issue 18 (4th August 2021) - Carstens, Matthew R.; Wasserfall, Clive H.; Acharya, Abhinav P.; Lewis, Jamal; Agrawal, Nikunj; Koenders, Kevin; Bracho-Sanchez, Evelyn; Keselowsky, Benjamin G.
Abstract : Microarrays, miniaturized platforms used for high-content studies, provide potential advantages over traditional in vitro investigation in terms of time, cost, and parallel analyses. Abstract : Microarrays, miniaturized platforms used for high-content studies, provide potential advantages over traditional in vitro investigation in terms of time, cost, and parallel analyses. Recently, microarrays have been leveraged to investigate immune cell biology by providing a platform with which to systematically investigate the effects of various agents on a wide variety of cellular processes, including those giving rise to immune regulation for application toward curtailing autoimmunity. A specific embodiment incorporates dendritic cells cultured on microarrays containing biodegradable microparticles. Such an approach allows immune cell and microparticle co-localization and release of compounds on small, isolated populations of cells, enabling a quick, convenient method to quantify a variety of cellular responses in parallel. In this study, the microparticle microarray platform was utilized to investigate a small library of sixteen generally regarded as safe (GRAS) compounds (ascorbic acid, aspirin, capsaicin, celastrol, curcumin, epigallocatechin-3-gallate, ergosterol, hemin, hydrocortisone, indomethacin, menadione, naproxen, resveratrol, retinoic acid, α-tocopherol, vitamin D3) for their ability to induce suppressive phenotypes in murine dendritic cells. Two complementary tolerogenic index ranking systems were proposed to summarize dendritic cell responses and suggested several lead compounds (celastrol, ergosterol, vitamin D3) and two secondary compounds (hemin, capsaicin), which warrant further investigation for applications toward suppression and tolerance.